2016
DOI: 10.21273/horttech.26.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cross- and Self-pollination on Fruit Set, Fruit Size, Seed Number, and Harvest Timing Among 13 Southern Highbush Blueberry Cultivars

Abstract: Cross-pollination has been associated with improved fruit set, weight, and shortened time to ripening in southern highbush blueberry [SHB (Vaccinium corymbosum interspecific hybrids)]. Because of this, growers commonly plant two or more cultivars in small blocks to facilitate cross-pollination. However, many SHB cultivars may vary in the degree of improvement in each parameter after cross-pollination. Understanding the impacts of cross-pollination on a particular cultivar is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 12 publications
0
16
1
1
Order By: Relevance
“…1.2) suggests that it is prudent to interplant whenever possible. Other studies have also shown that fruit mass can be increased when varieties are pollinated with pollen from other varieties (Bell et al, 2012;Harrison et al, 1993;Müller et al, 2013;Taber and Olmstead, 2016). In this study, the degree of benefit from inter-varietal pollen appeared to differ between varieties and while absolute positive effects were always detected, these were often not statistically significant.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…1.2) suggests that it is prudent to interplant whenever possible. Other studies have also shown that fruit mass can be increased when varieties are pollinated with pollen from other varieties (Bell et al, 2012;Harrison et al, 1993;Müller et al, 2013;Taber and Olmstead, 2016). In this study, the degree of benefit from inter-varietal pollen appeared to differ between varieties and while absolute positive effects were always detected, these were often not statistically significant.…”
Section: Discussionmentioning
confidence: 40%
“…For Suziblue and Twilight, intervarietal pollination also led to significant reductions in developmental time. Inter-varietal pollination has also been shown to decrease developmental time in other blueberry varieties such as Bluecrop, Bluegold, Legacy, Sierra, Toro and Patriot (Dogterom et al, 2000;Ehlenfeldt, 2001;Gupton and Spiers, 1994;Mackenzie, 1997;Müller et al, 2013;Taber and Olmstead, 2016). Choosing the correct pollen source appears to be especially important for varieties such as Eureka, Suziblue and Twilight as pollen quality is likely to have large consequences for yields and interplanting varieties to promote outcrossing therefore seems to be the best strategy for increased fruit mass and decreased developmental times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultivars differ in percent fruit set or seed set because of differing bloom periods and associated differences in weather (Arrington and DeVetter, 2017), differences in attractiveness of the flowers to pollinators (Courcelles et al, 2013), and genetic differences in self-or cross-compatibility and pollen quantity or quality (e.g., Brewer and Dobson, 1969;Chavez and Lyrene, 2009;Ehlenfeldt and Kramer, 2012;MacKenzie, 1997;Rabaey and Luby, 1988;Vander Kloet, 1983). As a result, cultivars have been found to differ in the seeds/berry and, often as a result, berry size (Arrington and DeVetter, 2018;Brewer and Dobson, 1969;DeVetter et al, 2016;Eaton, 1967;Ehlenfeldt, 2001;Ehlenfeldt and Martin, 2010;Gupton, 1984;Gupton and Spiers, 1994;Jackson et al, 1972;Lang and Danka, 1991;Lyrene, 1989;Meader, 1936;Meader andDarrow, 1944, 1947;Moore et al, 1972;Morrow, 1943;Payne et al, 1989;Taber and Olmstead, 2016).…”
mentioning
confidence: 99%
“…Cultivars differ in the berry weight per seed (Bailey, 1938;Brewer and Dobson, 1969;Eaton, 1967;Gupton, 1984;Knight and Scott, 1964;Lyrene and Goldy, 1983;Meader and Darrow, 1944;Rabaey and Luby, 1988;Taber and Olmstead, 2016). It is possible that cultivars vary in growth hormones produced by the fertilized ovules or developing seeds (Mainland and Eck, 1968;Meader andDarrow, 1944, 1947;Moore et al, 1972).…”
mentioning
confidence: 99%